HUKUM JUAL BELI ANGSURAN (KREDIT) MENURUT SYARIAH - AL HAFID IBNU QAYYIM; RUJIANSYAH RUJIANSYAH (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2019)
The purpose of this study is to find out firsthand how the procedure of buying and selling installments (credit) and how the law according to sharia In order to encourage the development of Islamic economics, finance and Islamic banking nationally, efforts are needed to examine and expand scholarship related to buying and selling installments (credit) in accordance with sharia, for the convenience and security of the wider community, especially Muslims in buying and selling the installment system (credit) , so that Muslims do not hesitate and are afraid of falling into usury and the certainty of the law of buying and selling installments (credit) in Islamic sharia. The results of this study turned out to be buying and selling installments (credit) that may be according to sharia as long as there is no tyranny in it, there is no element of usury, and is done on a voluntary basis.